Pengaruh Harbolnas, Fitur Shopee Paylater dan Koin Shopee terhadap Perilaku Impulse Buying dengan Karakteristik Individu sebagai Variabel Intervening:: Studi Kasus Mahasiswa Kampus Islam di Sumatera Utara - Siregar, Yuni Maryam; Lestari, Annio Indah; Hasibuan, Reni Ria Armayani (Comit: Communication, Information and Technology Journal, 2024)
In an increasingly advanced era, humans are required to keep abreast of the times in order to keep pace with life. Technological advances in obtaining information are certainly very influential in the development of technology-based businesses. This study aims to determine the effect of Harbolnas, shopee paylater features and shopee coins on impulse buying behavior with individual characteristics as intervening variables (case study of Islamic campus students in North Sumatra). This research was conducted with a quantitative approach method and used 3 independent variables, namely Harbolnas (X1), Shopee Paylater (X2) and Shopee Coins (X3) and one dependent variable, namely impulse buying (Y) and one intervening variable, namely individual characteristics (Z). . The sample used in this study were students of an Islamic campus in North Sumatra with 99 samples of shopee users. The type of data used is by distributing questionnaires. While the technique that researchers use to analyze is path analysis. The results of this study indicate that (i) the Harbolnas variable has no significant effect on the impulse buying variable (ii) the shopee paylater feature variable has a positive and significant direct effect on impulse buying (iii) the shopee coin variable has a positive and significant direct effect on impulse buying ( iv) individual characteristic variables cannot mediate harbolnas variable on impulse buying behavior (v) individual characteristic variable is able to mediate shopee paylater variable on impulse buying behavior (vi) individual characteristic variable is able to mediate shopee coin variable on impulse buying behavior. (vii) individual characteristic variables have a negative and significant effect on impulse buying. Keywords: Harbolnas, Shopee Paylater Features, Shopee Coins, Impulse Buying, Individual Characteristics